Modeling the relationship between economic complexity and environmental degradation: Evidence from top seven economic complexity countries - Martins, J.; Adebayo, T. S.; Mata, M. N.; Oladipupo, S. D.; Adeshola, I.; Ahmed, Z.; Correia, A. B. (Frontiers in Environmental Science, 2021)
The continuous growth in CO2 emissions of nations around the globe has made achieving the aim of sustainable development extremely challenging. Therefore, the current research assesses the connection between CO2 emissions and economic complexity in the top 7 economic complexity countries while taking into account the role of economic growth, renewable energy consumption, and globalization for the period between 1993 and 2018. The research aims to answer the following questions: 1) What is the association between CO2 and the regressors in the long-run? 2) What are the effects of renewable energy consumption, economic growth, economic complexity, and globalization on CO2 emissions? The research utilized the CS-ARDL, CCEMG and panel causality approaches to investigate these interconnections. The empirical outcomes revealed that economic growth and economic complexity increase CO2 emissions while renewable energy consumption and globalization mitigate CO2 emissions. The outcomes of the causality test revealed a feedback causal connection between economic growth and CO2, while a unidirectional causality was established from economic complexity, globalization and renewable energy consumption to CO2 emissions in the top 7 economic complexity countries.